Study of the Organic Soil Modified by Alkyl Quaternary Ammonium in Water Pollution Treatment - Wang, Q.; Song, M.X.; Liu, X.M.; Nasier, A.; Zhu, W.Q. (Asian Journal of Chemistry, 2012)
Natural soil was modified by quaternary ammonium cationic surfactant octadecyl trimethyl ammonium chloride and characterized by Fourier transform infrared spectra and small angle X-ray diffraction. The results showed that the organic molecular chain had intercalated into the layers of natural soil layer lattice and arranged aslope by 50.2º. The adsorption capacity and the stability of octadecyl trimethyl ammonium chloride-modified and natural soil were compared by static and dynamic experiment respectively, which indicated that the CODCr of purified water was 18.11 mg L-1 and the CODCr removal efficiency was as high as 84.9 % by the modified soil as well as excellent stability. The experiment proved that octadecyl trimethyl ammonium chloride-modified soil exhibited good effect on wastewater purification and its application foreground was broad.